Pengaruh Brand Image dan Electronic Word Of Mouth (e-WOM) terhadap Minat Beli Jasa Wedding Organizer Mahar Agung Surabaya - Reza Dwi Firmansyah; Sugeng Purwanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
The use of wedding organizer services in Surabaya is increasingly varied every day. This aims to help organize weddings desired by consumers, thus making the competition between several wedding organizers in Surabaya more competitive. The various prices offered by wedding organizer services make their marketing affect consumers' buying interest. The results of the research are intended to determine the buying interest in wedding organizer services Mahar Agung Surabaya through the influence of Brand Image and Electronic Word Of Mouth (e-WOM). Through quantitative methods, data collection is carried out through survey results, to be analyzed through Partial Least Square (PLS) software. So that the findings from the study concluded that there was a positive influence of Brand Image and Electronic Word Of Mouth on Buying Interest.